Requirements for Using Interest Rates As An Operating Target for Monetary Policy : The Case of Tunisia - Durre, Alain; Chailloux, Alexandre; Laurens, Bernard (Washington, D.C. : International Monetary Fund, 2009)
This paper discusses the use of interest rates as the operating target for monetary policy in Tunisia and the roadmap for establishing the other building blocks of an inflation targeting framework. It argues that strengthening the effectiveness of the current monetary policy framework will facilitate the adoption of inflation targeting over time.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet